Predictors of patient safety culture in hospitals in Venezuela: A cross-sectional study - Chirinos Muñoz, Mónica Susana; Orrego, Carola; Montoya, Cesar; Suñol, Rosa (Medicine (Baltimore), 2021)
An organization's culture with regard to patient safety is important because it defines the beliefs and practices of the organization, and consequently its efficiency and productivity.Knowing the level of this and the factors that influence or not their dynamic represents a challenge, due to the degree of complexity and specificity of the elements involved.The aim of this study was to analyze predictors of patient safety culture in public and private hospitals and examining the factors that contribute to it, constructing a new and specific theoretical and methodological model.This study was carried out by reviewing medical records, detecting healthcare professionals directly involved in caring (N = 588), for patients in 2 public hospitals and 2 private hospitals in Venezuela (N = 566), conducting an "Analysis of Patient Safety Culture" questionnaire. The results were subsequently analyzed, derived 3 predictors factors and using a Patient Safety Culture Index (PSCI) for specific determination to evaluate patient safety culture level.The analysis showed that all hospitals had a "moderately unfavorable" PSCI (public = 52.96, private = 52.67, sig = 0.90). The PSCI was calculated by assessing the weight of the following factors in the index: occupational factors (factor loading = 32.03), communication factors (factor loading = 11.83), and organizational factors (factor loading = 9.10). Traumatology presented the lowest PSCI of all the care units, falling into the "unfavorable" category (36.48), and Laboratory the highest (70.02) (sig = 0.174), falling into the "moderately favorable" category. When analyzing professional groups, nurses had the highest PSCI, with a "moderately unfavorable" rating (PSCI = 61.1) and medical residents the lowest, falling into the "unfavorable" category (35.2). Adverse event reporting is determined by "management expectations and actions" (sig = 0.048) and "direct interaction with the patient" (sig = 0.049).The use of this theoretical and methodological approach in other contexts may provide a more objective system for identifying more specific needs and factors that influence in patient safety culture, and consequently, opportunities for improvement when constructing a patient safety culture in healthcare institutions. Efforts need to be made to improve safety culture in the hospitals studied, irrespective of whether they are public or private.